Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - WANG Yong-ping; LI Guo-yu; JIN Hui-jun; LU Lan-zhi; HE Rui-xia; ZHANG Peng (Journal of Mountain Science, 2016)
On-site monitoring is very important for understanding formation mechanisms of frost hazards frequently occurring in pipeline foundation soils and for designing and deploying according mitigative measures in permafrost regions. Significant thaw subsidence of ground surfaces along the China-Russia Crude Oil Pipeline (CRCOP) from Mo'he to Daqing, Heilongjiang Province, Northeast China have been observed at some segments underlain by ice-rich, warm (>1.0°C) permafrost since the official operation in January 2011. Recent monitoring results of the thermal states of foundation soils at the kilometer post (KP) 304 site along the CRCOP are presented in this paper. The results indicate that during the period from 2012 to 2014, shallow soils (at the depths from 0.8 to 4.0 m from ground surface) has warmed by approximately 1.0°C in the lateral range of 1.2 to 2.1 m away from the pipeline axis, and deeper permafrost (such as at the depth of 15 m, or the depth of zero annual amplitude of ground temperatures) by 0.08°C per year 4 m away from the pipe axis, and 0.07°C per year 5 m away from the pipeline axis. The results indicate an all-season talik has developed around and along the CRCOP. The thaw bulb, with a faster lateral expansion (compared with the vertical growth), enlarges in summer and shrinks in winter. This research will provide important references and bases for evaluating thermal influences of warm pipeline on permafrost and for design, construction, operation and maintenance of pipelines in permafrost regions.